Problem Identification and Business Plan of Beauty Clinics: Application of Qualitative Research Approaches - Devanty Anggraini; Ruth Agustina Sinaga; Surya Setyawan (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to pinpoint the fundamental challenges encountered by a beauty clinic in Jakarta and develop an appropriate business strategy through qualitative research methods. Data were gathered via in-depth interviews with 15 participants, consisting of 10 active clients, 5 inactive clients, 3 therapists, and 1 operational manager, complemented by participatory field observations conducted over a three-month period. The findings revealed four primary issues: inconsistent service quality, weak brand identity and differentiation, inadequate digital marketing strategies, and the absence of a customer loyalty system. In response to these findings, a business plan was formulated encompassing service standardization, brand repositioning, enhanced digital marketing optimization, and the creation of customer retention programs. This research underscores the significance of employing qualitative approaches to comprehend consumer expectations and formulate experience-driven service business development strategies. The implications of this study provide practical guidance for beauty clinic managers in designing customer-centric business models and offer methodological contributions to qualitative research applications in service industry contexts.